2013
DOI: 10.1371/journal.pone.0061512
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Drug Response and Efflux Transporters Associated with Drug Resistance in Pediatric High Grade Glioma and Diffuse Intrinsic Pontine Glioma

Abstract: Pediatric high-grade gliomas (pHGG), including diffuse intrinsic pontine gliomas (DIPG), are the leading cause of cancer-related death in children. While it is clear that surgery (if possible), and radiotherapy are beneficial for treatment, the role of chemotherapy for these tumors is still unclear. Therefore, we performed an in vitro drug screen on primary glioma cells, including three DIPG cultures, to determine drug sensitivity of these tumours, without the possible confounding effect of insufficient drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(80 citation statements)
references
References 59 publications
(39 reference statements)
2
72
1
Order By: Relevance
“…Similar disappointing results have been found with other chemotherapy combinations [44,45]. It has been demonstrated in vitro that DIPG cells are not technically chemotherapy resistant, but rather express drug efflux transporters extracellularly [46]. This may provide a focus for further research and a potential treatment paradigm.…”
Section: Diffuse Intrinsic Pontine Gliomasupporting
confidence: 56%
“…Similar disappointing results have been found with other chemotherapy combinations [44,45]. It has been demonstrated in vitro that DIPG cells are not technically chemotherapy resistant, but rather express drug efflux transporters extracellularly [46]. This may provide a focus for further research and a potential treatment paradigm.…”
Section: Diffuse Intrinsic Pontine Gliomasupporting
confidence: 56%
“…The lack of success in the results may be at least partly explained by the inability to deliver therapeutic agents to the CNS tumors across the blood-brain barrier (Laquintana et al 2009). Drug delivery to the brain is hampered by the presence of P-glycoprotein (P-gp, ABCB1), breast cancer resistance protein (BCRP, ABCG2), and multidrug resistance-associated proteins (MRPs, ABCC1) (Veringa et al 2013). In glioma cell lines, MDR1 Pglycoprotein and ABCC1 were shown to confer resistance to various anticancer drugs (Spiegl-Kreinecker et al 2002;Bronger et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies showed that in adults, Myocet ® has a longer half-life than standard doxorubicin, significantly less cardiotoxicity, and comparable antitumour efficacy [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…The brain exposure to this drug is, however, hindered by the bloodbrain barrier. Encapsulation of DXR in liposomal carriers has been shown to both reduce toxicities [3,4] and improve brain tumour exposure to doxorubicin [5]. Moreover, while…”
Section: Introductionmentioning
confidence: 99%